Pengaruh Metode Relaksasi Benson Terhadap Kualitas Tidur Pada Lansia Dengan Gangguan Tidur Di Rumah Pelayanan Sosial Lanjut Usia Pucang Gading - Deviana Nokia Rosza; Iskim Luthfa; Nutrisia Nu’im Haiya; Moch Aspihan (An-Najat, 2025)
Many elderly people's sleep needs are generally disturbed, both in quality and quantity. The impact of sleep disorders, if not handled properly, will result in physiological and psychological disorders. Benson relaxation therapy can be used as a non-pharmacological therapy for sleep quality disorders in the elderly. The aim of this study was to analyze the effect of providing the Benson relaxation technique on sleep quality for the elderly at the Pucang Gading Home for Elderly Social Services. This research uses a Quasy Experiment design. Sampling was taken using total sampling technique. The sample used was 105 elderly people who experienced sleep quality problems. Data collection used the Pittsburgh Sleep Quality Index (PSQI) questionnaire and statistical analysis used the Wilcoxon test. The results of the study showed that before administering Benson relaxation therapy the average sleep quality was poor at 62.9 and after the intervention the average sleep quality was in the good category 86.7. The results of research using the Wilcoxon test obtained a P value = 0.000 < 0.05, because the p value < α means that Benson relaxation therapy is effective on sleep quality in the elderly, so Ha is accepted. From the research that has been carried out, it is hoped that elderly people who experience sleep disorders can carry out Benson Relaxation Therapy well in order to overcome the problem of disrupting sleep quality.